IMMUNE PROFILING OF PATIENTS WITH ADVANCED SOLID TUMORS TREATED WITH INTRATUMORALLY ADMINISTERED CV8102 AS A SINGLE-AGENT OR IN COMBINATION WITH ANTI-PD-1 ANTIBODIES IN PHASE I CLINICAL TRIAL - Codo, Paula; Eigentler, Thomas; Heinzerling, Lucie; Krauss, Juergen; Weishaupt, Carsten; Ochsenreither, Sebastian; Lebbe, Celeste; Mohr, Peter; Oliva, Marc; Oberoi, Honey; Terheyden, Patrick; Perez, Jose Trigo; et al. (JOURNAL FOR IMMUNOTHERAPY OF CANCER, 2021)
CV8102 is a non-coding, non-capped RNA complexed with a carrier peptide activating the innate (via TLR7/8, RIG-I) and adaptive immune system.1 2 An ongoing phase I trial is investigating the intratumoral (i.t.) administration of CV8102 in patients with advanced cutaneous melanoma (cMEL), squamous cell carcinoma of the skin (cSCC) or head and neck (hnSCC) and adenoid cystic carcinoma (ACC), either as a single agent or in combination with systemic anti-PD-1 antibodies. Preliminary immune profiling results will be reported.<br
CRIS-Team WoS Importer:2022-04-15